Landslide mitigation strategies in southeast Bangladesh: Lessons learned from the institutional responses. (August 2021) - Sultana, Neegar; Tan, Shukui
Abstract: The paper examines how local-level institutions mitigate landslide hazards in southeast Bangladesh. In this context, sixteen sub-districts (Upazila) were selected as sample sites from the southeastern districts through disproportionate quota sampling for a sample survey. Forty-five officials were interviewed by using a semi-structured questionnaire at the local level. The study reveals two types of measures (i.e., structural and non-structural) that have been taken by local-level institutions under the National Plan of Disaster Management (NPDM) as there is no Landslide-specific Disaster Management Policy in southeast Bangladesh. The study explores that the structural measures (guide wall and retaining wall for slope stabilization, resettlement, small-scale plantation, etc.) are insufficient due to the financial constraints. The findings reveal that the emergency responses (eviction, temporary evacuation, dissemination of early warning, etc.) are adequate to reduce the landslide-induced causality; however, the non-structural measures (such as early warning system, housing facilities, community-based awareness-raising programs with more training and workshops, rehabilitation activities, etc.) need special attention to mitigate landslide hazards. The results also suggest that resettlement policy should consider the ethnic culture along with other regional factors of a diversified hilly environment. It also puts forward an institution-based solution, including a comprehensive official landslide database with sustainable hill management mechanisms. Such evidence epitomizes a significant foremost step in developing realistic mitigation strategies for landslide-prone areas with similar socio-economic, cultural, and regional settings like southeast Bangladesh. Highlights: Lack of Landslide-specific Disaster Management Policy in southeast Bangladesh. The structural measures are insufficient due to the financial constraints. The non-structural measures need special attention to mitigate landslide hazards. Resettlement policy should consider the ethnic culture along with other regional factors.